La Participation Citoyenne A La Gestion De La Municipalite De Guiglo En Cote d’Ivoire - Jean-Arsene, Guiriobe Paumahoulou (European Scientific Journal, ESJ, 2016)
These writings evaluate citizen participation in the management of municipality of Guiglo in Côte d’Ivoire. To do this, we interviewed, using individual semi-structured interviews, resource persons in this locality. From these interviews, it appears that there is no form of citizen participation in the management of that local authority, outside the municipal elections. However, local elected officials use various strategies such as the presence of representatives of populations at regular sessions of municipal councils to pretend they associate third parties in the management of their city. This lack of citizen participation is, ever so slightly, causing the mismatch between insiders’ local development projects provided by these municipalities and the real aspirations of the beneficiaries.